The relationship between burnout and spiritual intelligence among dental residents in Shiraz, Iran - Zahra Yaghoubi; Saber Babazadeh; Faezeh Karimzadeh Sharaf; Reyhaneh Shafieian; Arghavan Behbahanirad (Shiraz University of Medical Sciences, 2020)
Background: Burnout, as the consequence of uncontrolled chronic stress, can lead to less efficient clinical performance. Spiritual intelligence enables the individuals to manage their carrier more efficiently. The aim of this study was to explore the relationship between spiritual intelligence and burnout among dental residents. Methods: This analytic cross-sectional study included all dental residents in Shiraz Dental School during 2019, except for those who were no willing to participate in the study. Of 72 dental residents, 57 participated in the study and filled out the questionnaires. Maslach Burnout Inventory and King's Spiritual Intelligence Questionnaires were used to collect the data. The Maslach's Questionnaire consists of three domains: emotional exhaustion, depersonalization, and personal accomplishment. Results: The results showed that 91.2% of the participants experienced a high degree of reduced  personal accomplishment. Reduced personal accomplishment had a significant correlation with almost all spiritual intelligence dimensions: personal meaning (r=-0.345, P=0.009), transcendental awareness (r=-0.280, P=0.035), and conscious state expansion (r=-0.268, P=0.044). Moreover, personal meaning was inversely correlated with emotional exhaustion (r=-0.411, P=0.002). The scores of spiritual intelligence and burnout dimensions had no significant differences based on marital status, gender, and academic year, except for gender in critical thinking domain(P=0.020). Conclusion: The participants experienced high degrees of burnout in reduced personal accomplishment domain. The level of spiritual intelligence was moderate among the participants. In general, the higher scores of spiritual intelligence dimensions were correlated to higher personal accomplishment as a main dimension of burnout. Policy- makers should adopt methods to reduce burnout and improve spiritual dimensions.